Nitrificação e desnitrificação simultâneas em biofiltros aerados com alta densidade de lodo - Bezerra Filho, Weliton Freire (2015)
Population growth and aspects related to management water resources, make it extremely important to search for simple wastewater treatment systems, low cost and simplicity operational, capable of producing effluent with potential use for compatible many purposes. In this scenario, the use of aerated reactors as post-treatment of anaerobic effluent is shown quite promising for Brazilian reality. This work contributes to the development of new biofilter system for aerobic treatment of sewage, which is being developed at the Federal University of Rio Grande do Norte. The reactor uses corrugated conduit as cut filler, providing a high void ratio, and is capable of producing effluent with turbidity UT order of 1, 2 mg / L of TSS and COD of below 40 mg / L. IT IS objective of this work to investigate the nitrogen removal capacity by simultaneous nitrification and denitrification. The work was divided into four phases, in which has been changed air flow in the filters, and during step 4, introduced a supplementary source of carbon. The system proved to be effective regarding the removal of nitrogen. In the most efficient configuration It was able to remove 56% of the influent nitrogen, and the less efficient phase removal was 40%. The principal component analysis showed that the nitrification was the most important factor for the process. It was concluded that the system is able to remove nitrogen through nitrification and simultaneous denitrification. Furthermore, it is also important to mention that during the more than three years of the experiment duration was not required removal of retained sludge